An investigation on chemical bubble column using ultrasonic tomography for imaging of gas profiles - Rahiman, Mohd Hafiz Fazalul; Abdul Rahim, Ruzairi; Abdul Rahim, Herlina; Mohamad, Elmy Johana; Zakaria, Zulkarnay; Mohd Muji, Siti Zarin (Elsevier, 2014)
In this paper, we carried out a tomographic investigation of a chemical bubble column using ultrasonic sensor. The ultrasonic tomography sensing array was constructed to operate in transceiver-mode and was clamped on the exterior circumference of the column. The time-of-flight and arrival-time analysis was studied to obtain the signal information. Some experiments were carried out using known static profiles and were compared with the actual profiles. The findings showed promising results where the sensing array could detect gas bubble profiles down to 3 mm in diameter, and the conclusions were made at the end of the paper.